A teachers' grammar - Cose, R.A (Thomson,Heinle, 1992)
This reference for teachers of English, particularly those entering the profession, contains a concise survey of the major issues in English grammar. The book is suitable for teachers on CTEFLA/DTEFLA courses, trainees at teacher training colleges and undergraduates preparing to teach EFL